Perbedaan Pelaksanaan Terhadap Perencanaan Dan Cara Mengatasinya Pada Proyek Konstruksi - Gita Puspa Artiani; Fajar Eka Surya (Sekolah Tinggi Teknik - PLN, 2017)
Problems on the construction project going on for many things, but the cause that often arises is the difference in the implementation of the planning of the field, causing a large increase in funding costs. Their main work items that are not entered into the budget plan, and there are differences of specifications in the plans designed by the consultant is one of the problems that occur. This research was conducted by two methods, namely quantitative data collection Budget Plan in the form of data, and the data volume deviation value-added jobs. Then do the data collecting qualitative data collection questionnaire with interview preventive and corrective actions to address and prevent these problems happening in future hari.Hasil study showed an increase in the cost of Rp.444.094.874 up 18% of the value of the contract so that the required solution / settlement on these cost increases. Obtained results of the questionnaire in the form of preventive measures such as: the process of selecting a consultant planner more selective, rigorous monitoring plan when making volume measurements in the field, and double-check the results of the planning. Corrective actions include: held CCO (Contract Change Order), Addendum, plus work less, and hospitalization for selectively on the added job priority